Disruption of Energy Metabolism and Reactive Oxygen Species Homeostasis in Honglian Type-Cytoplasmic Male Sterility (HL-CMS) Rice Pollen - Wang Mingyue; Zhao Weibo; Feng Xiaoya; Chen Yi; Li Junhao; Fu Jinmei; Yan Yingchun; Chu Zhaohui; Huang Wenchao (Rice Science)
Honglian type-cytoplasmic male sterility (HL-CMS) is caused by the inter-communication between the nucleus and mitochondria. However, the mechanisms by which sterility genes regulate metabolic alterations and changes in mitochondrial morphology in the pollen of HL-CMS remain unclear. In this study, we compared the morphological differences between the pollen of the male sterile line YA and the near-isogenic line NIL-Rf6 using hematoxylin-eosin staining and 4ʹ,6-diamidino-2-phenylindole (DAPI) staining. HL-CMS is characterized by gametophytic sterility, where the aborted pollen grains are empty, and the tapetal layer remains intact. Transmission electron microscopy was employed to observe mitochondrial morphological changes at the microspore stage, revealing significant mitochondrial alterations, characterized by the formation of 'large spherical mitochondria', occurred at the binucleate stage in the YA line. Additionally, metabolomics analysis revealed decreased levels of metabolites associated with the carbohydrate and flavonoid pathways. Notably, the decrease in flavonoids was found to contribute to an elevation in reactive oxygen species (ROS) levels. Therefore, we propose a model in which rice fertility is modulated by the levels of pollen carbohydrates and flavonoid metabolites, with impaired mitochondrial energy production and reduced flavonoid biosynthesis as the main causes of ROS accumulation and pollen abortion in rice.